Type of education and life experiences in the dual career - Graczyk, M.; Nawrocka, A.; Wylleman, P.; Moska, W.; Tomiak, T.; Lachowicz, M.; Drobnik, P. (Baltic Journal of Health and Physical Activity, 2018)
Background: The objective of this study was to check whether the type of education is related to the development of a dual career in professional sport.